Heterosubtypic immunity to H7N9 influenza virus in isogenic guinea pigs after infection with pandemic H1N1 virus. Issue 49 (8th December 2015) - Wiersma, Lidewij C.M.; Vogelzang-van Trierum, Stella E.; Kreijtz, Joost H.C.M.; van Amerongen, Geert; van Run, Peter; Ladwig, Mechtild; Banneke, Stefanie; Schaefer, Hubert; Fouchier, Ron A.M.; Kuiken, Thijs; Osterhaus, Albert D.M.E.; Rimmelzwaan, Guus F.
Highlights: Influenza A(H1N1)pdm09 virus infection provides heterosubtypic immunity to A(H7N9). First time heterosubtypic immunity is demonstrated in isogenic guinea pigs. No sterile immunity but decrease in extent and duration of virus shedding. This model can help elucidate effect of cell mediated immunity on transmission. Abstract: Heterosubtypic immunity is defined as immune-mediated (partial) protection against an influenza virus induced by an influenza virus of another subtype to which the host has not previously been exposed. This cross-protective effect has not yet been demonstrated to the newly emerging avian influenza A viruses of the H7N9 subtype. Here, we assessed the induction of protective immunity to these viruses by infection with A(H1N1)pdm09 virus in a newly developed guinea pig model. To this end, ten female 12–16 week old strain 2 guinea pigs were inoculated intratracheally with either A(H1N1)pdm09 influenza virus or PBS (unprimed controls) followed 4 weeks later with an A/H7N9 influenza virus challenge. Nasal swabs were taken daily and animals from both groups were sacrificed on days 2 and 7 post inoculation (p.i.) with A/H7N9 virus and full necropsies were performed. Nasal virus excretion persisted until day 7 in unprimed control animals, whereas only two out of seven H1N1pdm09-primed animals excreted virus via the nose. Infectious virus was recovered from nasal turbinates, trachea and lung of all animals at day 2 p.i., but titers were lower for H1N1pdm09-primed animals, especially in the nasal turbinates. By day 7 p.i., relatively high virus titers were found in the nasal turbinates of all unprimed control animals but infectious virus was isolated from the nose of only one of four H1N1pdm09-primed animals. Animals of both groups developed inflammation of variable severity in the entire respiratory tract. Viral antigen positive cells were demonstrated in the nasal epithelium of both groups at day 2. The bronchi(oli) and alveoli of unprimed animals showed a moderate to strong positive signal at day 2, whereas H1N1pdm09-primed animals showed only minimal positivity. By day 7, only viral antigen positive cells were found after H7N9 virus infection in the nasal turbinates and the lungs of unprimed controls. Thus infection with H1N1pdm09 virus induced partially protective heterosubtypic immunity to H7N9 virus in (isogenic) guinea pigs that could not be attributed to cross-reactive virus neutralizing antibodies.